The landscape of strategic health purchasing for universal health coverage in Burkina Faso: insights from five major health financing schemes - Kiendrébéogo, Joël; Tapsoba, Charlemagne; Kafando, Yamba; Kaboré, Issa; Sory, Orokia; Yaméogo, S. Pierre (Health systems & reform, 2022)
Strategic health purchasing is a key strategy in Burkina Faso to spur progress toward universal health coverage (UHC). However, a comprehensive analysis of existing health financing arrangements and their purchasing functions has not been undertaken to date. This article provides an in-depth analysis of five key health financing schemes in Burkina Faso: Gratuité (a national free health care program for women and children under age 5), crédits délégués (delegated credits), crédits transférés (transfers to municipalities), community-based health insurance, and occupation-based health insurance. This study involved a document review and complementary key informant interviews using the Strategic Health Purchasing Progress Tracking Framework developed by the Strategic Purchasing Africa Resource Center (SPARC). Data were collected using the framework’s accompanying Microsoft Excel-based tool. We analyzed the data manually to examine and identify the strengths and weaknesses of governance arrangements and purchasing functions and capacities. The study provides insight into areas that are working well from a strategic purchasing perspective and, more importantly, areas that need more attention. Areas for improvement include low financial and managerial autonomy for some schemes, weak accountability measures, lack of explicit quality standards for contracting and for service delivery, budget overruns and late provider payment, provider payment that is not linked to provider performance, fragmented health information systems, and information generated is not linked to purchasing decisions. Improvements in purchasing functions are required to address shortcomings while consolidating achievements. This study will inform next steps for Burkina Faso to improve purchasing and advance progress toward UHC.